IMPACT OF ANDROGEN DEPRIVATION THERAPY AND OPEN RADICAL RETROPUBIC PROSTATECTOMY ON LOWER URINARY TRACT SYMPTOMS IN PATIENTS WITH PROSTATE CANCER - Dinić, Ljubomir A; Ignjatović, Ivan; Bašić, Dragoslav; Dinić, Vesna; Veljković, Andrej; Skakić, Aleksandar; Đorđević, Miodrag; Laketić, Darko; Mihajlović, Marija; Janić, Jovan; Potić, Milan (Acta medicae Medianae, 2024)
The aim of this study was to show the impact of open radical prostatectomy (ORP) and primary hormone therapy on lower urinary tract symptoms (LUTS) and quality of life (QoL) related to these symptoms based on the International Prostate Symptom Score (IPSS). A total of 128 patients with localized prostate cancer were analyzed and divided into two groups. The first group consisted of subjects who underwent ORP, and the second group consisted of subjects who were primarily treated with hormone therapy for 12 months. To assess the impact of ORP and hormone therapy on LUTS and QoL, the IPSS and IPSS QoL questionnaires were used before the start of treatment and after 3, 6 and 12 months from the start of treatment. In both groups of subjects, the IPSSt score consistently significantly decreased during the follow-up period compared to the baseline (p < 0.001 for all). After 12 months IPSSt and IPSSv were significantly higher in group with hormonal therapy compared to ORP group (p < 0.001) and IPSSs was significantly higher ORP group compared to hormonal therapy group. In both groups of subjects, IPSS QoL consistently decreased significantly during the follow-up period (p < 0.001). IPSS Qol was significantly higher in ORP group compared to hormonal therapy group at baseline (p < 0.001), after 3 months (p=0.003), after 6 months (p = 0.002). ORP and hormone therapy as the primary treatment methods for patients with localized PC led to a statistically significant decrease in IPSS scores and a clinically significant improvement in LUTS. Also, QoL related to LUTS significantly improved in both groups of subjects after 12 months.